Estudio de lahares emplazados en el valle de Ubinas (sur del Perú) en febrero del 2016 - Mariño Salazar, Jersy (2018)
[ENG] A new eruptive episode of the Ubinas volcano initiated in September 2013 and ended in February 2017. Due to the intense rainfall that occurred in January and February of 2016, lahars flowed down through the rivers of the Ubinas valley between 7 and 28 February. The most voluminous lahar occurred on the 12 in the Para River, other lahars occurred on the 11 and 22 in the Volcanmayo-Ubinas River together with another event not precisely dated in February in the Anascapa River. The most voluminous lahar deposits covered about 324,000 m2 and reached an estimated volume between 65,000 and 160,000 m3. The second voluminous lahar on 22 February in the Volcanmayo-Ubinas River emplaced deposits in an area of about 120,000 m2 while its average volume was estimated to range between 25,000 and 60,000 m3. Both lahars destroyed farmlands, bridges, roads, and irrigation water channels, totaling a loss of about 1 million US dollars.